DETERMINATION OF TRACE RESIDU E S LEVEL OF PESTICIDES IN SOME VEGETABLES GROWING IN ALGERIA BY GC/µECD AND GC/MS - Mebrouki, S; Zerrouki, H; Belfar, M.L; Douadi, A; Moussaoui, Y (university of el oued/جامعة الوادي, 2021)
An analytical multiresidue method for the simultaneous determination of various classes of p esticides in vegetables ( tomato , pepper, hot pepper and potato ) was developed. Vegetable samples are extracted with acetonitrile. Final determination was mad e by gas chromatography with µ Electron Capture D etection (µ ECD) for organochloride pesticides . Organophosphorus, pyrithrinoids and other pesticides analysis was carried out by gas chromatography coupled with mass spectrometry in the selected ion monitori ng (SIM) mode. The identification of compounds was based on retention time and on comparison of the primary and secondary ions. Recovery studies were performed at various fortification levels of each compound and the rec overies obtained ranged from 70% to 127 % with relative standard deviations lower than 8 %. The method showed good linearity over the range studied and the detection and quantification limits for the pe sticides studied varied from 0.015 to 0.030 µg.g 1 and 0.05 to 0.1 µg.g 1 , respectively. Th e proposed method was used to determine pesticides levels in peppers , hot pepper and tomatoes grown in multichapelle greenhouses at Biskra region and potato grown at Setif region in Algeria
Article
Keywords: Keywords: Pesticides residue; Hot pepper, Pepper; Tomato; Potato; GC/µECD; GC/MS.